Epitaxial growth of oriented prussian blue analogue derived well-aligned CoFe2O4 thin film for efficient oxygen evolution reaction - Lei, Song; Li, Qiao-Hong; Kang, Yao; Gu, Zhi-Gang; Zhang, Jian (Applied catalysis. B, Environmental, 2019)
We first developed a well-aligned mesoporous CoFe2O4 thin film from surface epitaxial growth of oriented CoFe-based prussian blue analogue thin film (CoFe-PBA thin film) for efficient electrocatalytic OER. CoFe-PBA thin film with preferred [100] orientation is first prepared on the substrate surface by employing liquid-phase epitaxial method without any structure-directing surfactants. After thermal pyrolysis, such CoFe-PBA thin film was transformed into well-aligned mesoporous CoFe2O4 thin film with remarkable catalytic performance and durable stability. This study provides an effective paradigm for preparing binder-free, self-support and low-cost spinel oxide electrocatalyst for efficient OER derived from surface epitaxial growth of oriented PBA thin film. [Display omitted] •Epitaxial growth of oriented prussian blue analogue derived a bimetallic oxide film.•Obtained CoFe2O4 film has higher electrocatalytic OER than commercial RuO2.•Homogeneous and continuous bimetallic oxide film increased the OER performance.•Synergistic effect of Co and Fe promote the low-cost and high-efficient OER. The development of cost-effective, high-efficiency, and non-noble metal based electrocatalysts for oxygen evolution reaction (OER) is considered to be the most pivotal portion for electrochemical water splitting to generate renewable energy. Herein, well-aligned mesoporous CoFe2O4 thin film is first developed from surface epitaxial growth of oriented CoFe-based prussian blue analogue thin film (CoFe-PBA thin film) for efficient electrocatalytic OER. CoFe-PBA thin film with preferred [100] orientation is first prepared on the substrate surface by employing liquid phase epitaxial method without any structure-directing surfactants. After thermal pyrolysis, such CoFe-PBA thin film was transformed into well-aligned mesoporous CoFe2O4 thin film. Interestingly, the self-support CoFe2O4 thin film electrode with the mass loading of 1.6 mg cm−2 delivers an oxygen evolution current density of 10 mA cm−2 at an overpotential of 266 mV and exhibits durable stability in 1 M KOH aqueous solution. The remarkable and stable catalytic performance of the CoFe2O4 thin film can be mainly owing to the mesoporous structure of CoFe2O4, efficient charge/electron transfer, the numerous exposed active sites, and the well-structured configuration of the electrode. Hence, this work provides an effective paradigm for preparing binder-free, self-support, and low-cost spinel oxide electrocatalyst for efficient OER derived from surface epitaxial growth of oriented PBA thin film.